Some Relevant Aspects about the New Law on Prevention and Elimination of Bureaucratic Barriers - Bullard González, Alfredo (2017)
On December 8, 2016, the Executive, within the framework of the powers delegated by the Congress of the Republic through Law N°. 30506, published Legislative Decree N° 1256 in the Peruvian newspaper “El Peruano”, about “the Law on Prevention and Elimination of Bureaucratic Barriers”. The interview has the purpose of giving a general overview, through the analysis made by Alfredo Bullard.